An Analysis of Écriture Féminine In the Selection Series: The One (2014) Novel - Farrah Halimatussadyah (Passage, 2019)
This paper aims to investigate écriture féminine features in The Selection Series: The One novel written by Kiera Cass (2014). Female writers of dystopian literary works have increased in the past current years. The fact that the story of The Selection Series by Kiera Cass is narrated from a female perspective in a patriarchal country has drawn a connection to feminist study. This research used descriptive qualitative method and textual analysis that employs the theory of Écriture féminine by Helene Cixous (1976) and patriarchy by Gerda Lerner (1986). It is found that two primary features of écriture feminine, namely patriarchy and bisexual writing, are depicted in the novel as being interrelated. Patriarchy in the novel is mostly found in public sphere; therefore, a large amount of evidence of bisexual writing is found as responses to the patriarchal system. Three main forms of bisexual writing are found in the novel: negotiation, empowerment, and plurality. It seems that Kiera Cass successfully adapts écriture féminine in her novel. However, the end of the story of The One (2014) also implies that the deconstruction of patriarchy occurrs when there are acceptance and willingness of plurality, not only from women but also from men. Keywords: bisexual writing, dystopia, écriture feminine, patriarchy.